Nanotechnology : importance and applications - Fulekar, M.H (I. K. International Publishing House Pvt., 2011)
Highlights the latest developments and advances in the field of nanoscience and nanotechnology and their applications in the design and development of material science and devices, energy, drug delivery, cosmetics, biology, biotechnology, tissue engineering, bioinformatics, information technology, agriculture and food, environmental protection, health risk, ethics, and regulations.